A intuição clínica: entre Espinosa e Deleuze - Azevedo, Adriana Barin de (2013)
This work intends to show a way of thinking and practicing clinic inspired by Benedict de Spinoza and Gilles Deleuze's philosophy. Our reading of Spinoza's philosophy follows especially the one by Deleuze of it. With these authors, we can speak of a clinic that is concerned with lodging, caring and treating an individual, starting with the question of what he or she can do. This way, we realize that no individual lives the same change of affections, since it is always a singular experience. For Spinoza, the individual is a singular power (potentia), which varies through situations of suffering and joy. Even having a minimal power (potentia), even being very sad, an individual is always perfect, that is, he or she lacks nothing. These authors tell us that the idea of lacking is connected to interpretations and classifications that are the product of our imagination, which comprehends the affections abstractly. In order to show this process, we refer to Fernand Deligny's work with autistic children. This author lodges these children without understanding their autistic condition, marked by the absence of language as a limitation. He is interested in gestures and paths that express what these children are able to do. In his work he uses the concept of net as what allows bodies to participate in a single common plan. We think that this net concept echoes what Spinoza calls living under the guidance of reason, since what is rational for this author is connected with lodging in a common plan of composition. The clinic involve this kind of rational knowledge and, besides, an intuitive knowledge that allows us to understand an individual in his or her own singular power (potentia), that is, in what he or she can compose with everyone. We deal with this kind of clinical experience in a teaching-learning situation, in which a group of teachers show us a way of weaving a net by inventing formation practices. In this process, both teachers and students learn about their own singular power (potentia)